2022
DOI: 10.1007/s12038-022-00288-1
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of host microRNAs in flavivirus-induced neuropathology: An update

Abstract: Flaviviruses are a spectrum of vector-borne RNA viruses that cause potentially severe diseases in humans including encephalitis, acute-flaccid paralysis, cognitive disorders and foetal abnormalities. Japanese encephalitis virus (JEV), Zika virus (ZIKV), West Nile virus (WNV) and Dengue virus (DENV) are globally emerging pathogens that lead to epidemics and outbreaks with continued transmission to newer geographical areas over time. In the past decade, studies have focussed on understanding the pathogenic mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 160 publications
0
0
0
Order By: Relevance
“…Among these five proteins, we identify DDX1, an important helicase involved in host-defense mechanisms during viral infections [39]. NKRF is a regulator of DHX15, another RNA helicase involved in RNA processing and antiviral innate immunity [40], which was also seen to be inhibited by miR-301a during JEV infection [41]. Another example is NUFP2, a FMR1-interacting protein directly antagonized by the sfRNA of ZIKV [42].…”
Section: Resultsmentioning
confidence: 99%
“…Among these five proteins, we identify DDX1, an important helicase involved in host-defense mechanisms during viral infections [39]. NKRF is a regulator of DHX15, another RNA helicase involved in RNA processing and antiviral innate immunity [40], which was also seen to be inhibited by miR-301a during JEV infection [41]. Another example is NUFP2, a FMR1-interacting protein directly antagonized by the sfRNA of ZIKV [42].…”
Section: Resultsmentioning
confidence: 99%
“…Building upon initial observations, we posited that SCFAs could modulate microglial function by intricately adjusting their miRNA profiles, thereby influencing key inflammatory pathways. Previous studies have established the pivotal role of miRNAs in a host of cellular mechanisms, especially in the context of flavivirus infections ( 38 ). A pertinent question for future research is whether the shifts we observed in miRNA expression profiles and their downstream effects are attributable to HDAC inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…These multifarious molecules wield the potential to impact viral replication, temper the host's inflammatory response, fine-tune the expression of signaling molecules, and even shape the presentation of viral antigens. This discernment unveils an additional stratum of complexity within the molecular apparatus that underpins the intricate interplay between viruses and their hosts [5].…”
Section: Introductionmentioning
confidence: 93%